2021
DOI: 10.1155/2021/5792130
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of QingHuaZhiXie Prescription Regulating TLR4-IECs Pathway in the Intervention of Diarrhea Predominant Irritable Bowel Syndrome

Abstract: To investigate the effect and mechanism of QingHuaZhiXie prescription on diarrhea predominant irritable bowel syndrome (D-IBS), animal models of rats were used in this study. 48 rats were randomly divided into 6 groups, containing one control group, one animal model group (D-IBS group), and four drug intervention groups (low, medium, and high dosage of QingHuaZhiXie prescription and trimebutine maleate intervention group). Abdominal withdrawal reflex (AWR) and Bristol stool form scale were recorded; the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The TLR4-MyD88-transforming growth factor β-activated kinase1-NF-kB pathway is induced by wogonin to suppress inflammatory response and the down-regulation of CLDN-1 and ZO-1 in Caco-2 cells ( 102 ). IBS-D rats treated with QingHuaZhiXie prescription, a Chinese herbal compound prescription, showed that occludin, CLDN-1 and ZO-1 expression were restored in colon tissue by inhibiting the TLR4/MyD88/NF-κB pathway, which is accompanied by the improved symptoms of diarrhea and intestinal hypersensitivity ( 103 ).…”
Section: Discussionmentioning
confidence: 99%
“…The TLR4-MyD88-transforming growth factor β-activated kinase1-NF-kB pathway is induced by wogonin to suppress inflammatory response and the down-regulation of CLDN-1 and ZO-1 in Caco-2 cells ( 102 ). IBS-D rats treated with QingHuaZhiXie prescription, a Chinese herbal compound prescription, showed that occludin, CLDN-1 and ZO-1 expression were restored in colon tissue by inhibiting the TLR4/MyD88/NF-κB pathway, which is accompanied by the improved symptoms of diarrhea and intestinal hypersensitivity ( 103 ).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of individual cytokines responsible for barrier dysfunction in IBS-D will enable new therapeutic options. In this way, Huang and co-workers were able to identify a herbal mixture called "QingHuaZhiXie", which suppressed inflammatory factors and TLR4/MyD88/NF-κB pathway proteins, ultimately leading to increased protein levels of occludin and claudin-1 [33].…”
Section: Discussionmentioning
confidence: 99%